The fixed idea of old splendour: the Five Churches Restoration Plan completed (Bulletin KNOB, 1991)
The ambitious Utrecht Five Churches Restoration Plan, which execution started in 1968, closed with the festive opening of Utrecht Cathedral in 1988 and was awarded the silver medal of Europa Nostra. However, the project was criticized as well. Discussion ran high on the notion of restoration, on the admissibility of the reconstruction of disappeared elements and how to handle the authentic material the monument had been constructed of.Criticism in retrospect seems easy. But, not influenced by the problems of practice, criticism at some distance can be an advantage to the judgement of the final results of restoration. French gothic having found her purest expression in the choir of Utrecht cathedral, the starting point of architect T. van Hoogevest and his adviser Th. Haakma Wagenaar was reconstruction of the gothic ornamentation to complete the restorations as starled by Kamperdijk and Nieuwenhuis in the previous century and continued by Slothouwer from 1921 to 1938.Like this was the case in the 19th century some farreaching reconstructions are not always based on reliable sources. Van Hoogevest 'corrected' former structural alterations and restorations as well. Incited by the research of Haakma Wagenaar, which was mainly based on the rediscovery of old splendour, the restoration committee tried to embellish the cathedral in a historizing way, assuring that the historically grown situation constantly was taken into consideration.Sources on the cathedral's original ornamentation are extremely scarce. Therefore generally accepted principles of the period or typical features of the architects involved were taken as a guide. As in Neo-Gothic times the past was considered to be makeable. A-historical additions were inspired with aesthetic arguments and (neo-)gothic ornamentation. Sometimes even pinnacles were put up, never having been planned there before. But the design of these elements gives the impression to be authentic and mislead the spectator who is ignorant of the building's history.In this way all of the cuirasses of Nieuwenhuis' windows (1882-'84) in the Jacobichurch were removed during the last restoration. The loss of these traceries, only removed to make way for Haakma Wagenaar's 'correct' plantasies, must be regretted, all the more because these designs partly were based on the church's authentic Windows. Constructive restoration had consequences for the appearance of these five Churches as well.Every restoration for reasons of maintenance and embellishment means a loss of authentic materials with data on the building's history. Van Hoogevest stressed the contrast of the Gothic choir and the Romanesque nave and transept of the Church of St. John. This intensification of the Romanesque character as striven after during the last restoration resulted in a Church of St. John more Romanesque than ever before.Paradoxically enough it was necessary to pull down the largest part of the authentic Romanesque tuff. Since the cyclone of 1674 the five churches have not been so 'perfect' and complete. To justify these reconstructions historical representations of a lost splendour are used, which certainly do not render architectural reality and can be interpreted in several ways. In practice this mostly leads to a highly subjective interpretation.The monument obtains an aesthetical function and is adapted to the ideal of the restorers, often at the cost of historical substance. The churches have been 'enriched' with some new additions in old splendour, which create the appearance of authenticity. These notions on restoration have their origin in the 19th century and in Romanticism.The original state of a monument can be transformed anew and even improved according to the wishes of the restorer. These wishes have nothing to do with the demands of contructive justification or usage. In Utrecht the function of churches for the reformed worship has been neglected. Anno 1988 the archetype of the gothic cathedral is almost complete.